Clinical and genetic characteristics in pancreatic cancer from Chinese patients revealed by whole exome sequencing - He, Yonggang; Huang, Wen; Tang, Yichen; Li, Yuming; Peng, Xuehui; Li, Jing; Wu, Jing; You, Nan; Li, Ling; Liu, Chuang; Zheng, Lu; Huang, Xiaobing (Frontiers in Oncology, 2023)
Background Pancreatic ductal adenocarcinoma (PDAC) is one of the most fatal malignancies worldwide, mostly as a result of the absence of early detection and specific treatment solutions. Consequently, identifying mutational profiles and molecular biomarkers is essential for increasing the viability of precision therapy for pancreatic cancer. Methods We collected blood and tumor tissue samples from 47 Chinese pancreatic cancer patients and used whole-exome sequencing (WES) to evaluate the genetic landscape. Results Our results showed the most frequently somatic alteration genes were KRAS (74.5%), TP53(51.1%), SMAD4 (17%), ARID1A (12.8%), CDKN2A (12.8%), TENM4 (10.6%), TTN (8.5%), RNF43(8.5%), FLG (8.5%) and GAS6 (6.4%) in Chinese PDAC patients. We also found that three deleterious germline mutations (ATM c.4852C>T/p. R1618*, WRN c.1105C>T/p. R369*, PALB2 c.2760dupA/p. Q921Tfs*7) and two novel fusions (BRCA1-RPRML, MIR943 (intergenic)-FGFR3). When compared to the Cancer Genome Atlas (TCGA) database, there is a greater mutation frequency of TENM4 (10.6% vs. 1.6%, p = 0.01), GAS6(6.4% vs. 0.5%, p = 0.035), MMP17(6.4% vs. 0.5%, p = 0.035), ITM2B (6.4% vs. 0.5%, p = 0.035) and USP7 (6.4% vs. 0.5%, p= 0.035) as well as a reduced mutation frequency of SMAD4 (17.0% vs. 31.5%, p = 0.075) and CDKN2A (12.8% vs. 47.3%, p < 0.001) were observed in the Chinese cohort. Among the 41 individuals examined for programmed cell death ligand 1(PD-L1) expression, 15 (36.6%) had positive PD-L1 expression. The median tumor mutational burden (TMB) was found to be 12muts (range, 0124). The TMB index was higher in patients with mutant-type KRAS MUT/TP53 MUT (p < 0.001), CDKN2A (p = 0.547), or SMAD4 (p = 0.064) compared to patients with wild-type KRAS/TP53, CDKN2A, or SMAD4. Conclusions We exhibited real-world genetic traits and new alterations in Chinese individuals with cancer of the pancreas, which might have interesting implications for future individualized therapy and medication development.